PERBEDAAN SEMANTIS PREPOSISI SPASIAL 往 WANG DAN 向XIANG - Trihardini, Ayu; Sutami, Hermina (Bambuti | Fakultas Bahasa dan Budaya Universitas Darma Persada, 2026)
Spatial concepts help us in acquisition of knowledge. In Mandarin Chinese language, spatial concepts such as direction and location are expressed through the use of spatial prepositions. This paper presents a semantic analysis of the spatial prepositions 往 wǎng and 向 xiàng. This study aims to determine the distribution of nouns accompanying the two spatial prepositions. The method used is contrastive analysis with semantic classification. Nida's meaning field theory serves as a theoretical foundation. The research data were obtained from the Sketch Engine Chinese Web corpus 2017 Simplified zhTenTen17, consisting of 100 constructions containing 往 wǎng and 向 xiàng. The obtained noun types were cross-checked and verified with native speakers. The spatial prepositions 往 wǎng and 向 xiàng are one of the difficulties in learning Chinese. This is the main reason for this study. Research on Mandarin Chinese spatial prepositions can help Chinese learners visualize how native speakers think about spatial concepts. By understanding how the natives think, learners are expected to be able to produce more accurate speech. The results of this study indicate that only certain types of nouns can collocate with each of the spatial prepositions 往 wǎng or 向 xiàng. There is a similarity in meaning between 往 wǎng and 向 xiàng, namely expressing the process of achieving a goal, but the two prepositions are not completely interchangeable in their use.